“Deshidratación por flujo de aire caliente de pulpa de caracol gigante megalobulimux maximus” - Ramos Araujo, Jacinto (2009)
The aim of the present work was to determine the appropriate parameters for the conservation of the giant snail flesh (Megalobulimus maximus) for human consumption. For the analysis of the proximal pulp giant snail, in fresh state, were the following: 15.32% protein, 2.86% fat, 1.54% ash, 79.64% moisture and 0.64% carbohydrates. The snails were killed by immersion in water and subsequent heating from ambient temperatura, 27ºC, to 55ºC, in a time of 23.5 minutes; on the other hand, debugging is performed by immersing the pulp solution to 4% acetic acid for a time of 5 minutes at room temperatura. Dehydration of the giant snail flesh was in convective hot air dryer at temperaturas of 40°C, 50°C and 60°C with an air velocity of 1.2 m/s. With the data obtained during drying process were drawn charts for weight and water content as a function of time for each temperatura considered, which allowed us to determine the kinetics of drying of the snail flesh, which determined the kinetics and the drying rate increases with increasing temperaturas. The diffusion coefficient of water increases from 8.76 x 10-12 m2/s to 1.49 x 10-11 m2/s for temperatures of 40ºC to 60°C, respectively. The rehydration kinetics of the giant snail pulp, allowed to estímate the water holding capacity and adequate rehydration times were 22.33, 26.00 and 28.5 hours for drying temperaturas of 40°C, SOºC and 60°C, respectively.